Chlorine partitioning in the lowermost Arctic vortex during the cold winter 2015/2016 - Marsing, Andreas; Jurkat-Witschas, Tina; Grooß, Jens-Uwe; Kaufmann, Stefan; Heller, Romy; Engel, Andreas; Hoor, Peter; Krause, Jens; Voigt, Christiane (Atmospheric Chemistry and Physics, 2019)
Activated chlorine compounds in the polar winter stratosphere drive catalytic cycles that deplete ozone and methane, whose abundances are highly relevant to the evolution of global climate. The present work introduces a novel dataset of in situ measurements of relevant chlorine species in the lowermost Arctic stratosphere from the aircraft mission POLSTRACC–GW-LCYCLE–SALSA during winter 2015/2016. The major stages of chemical evolution of the lower polar vortex are presented in a consistent series of high-resolution mass spectrometric observations of HCl and ClONO2. Simultaneous measurements of CFC-12 are used to derive total inorganic chlorine (Cly) and active chlorine (ClOx). The new data highlight an altitude dependence of the pathway for chlorine deactivation in the lowermost vortex with HCl dominating below the 380 K isentropic surface and ClONO2 prevailing above. Further, we show that the Chemical Lagrangian Model of the Stratosphere (CLaMS) is generally able to reproduce the chemical evolution of the lower polar vortex chlorine budget, except for a bias in HCl concentrations. The model is used to relate local measurements to the vortex-wide evolution. The results are aimed at fostering our understanding of the climate impact of chlorine chemistry, providing new observational data to complement satellite data and assess model performance in the climate-sensitive upper troposphere and lower stratosphere region.